Боулинг-79: роман / Анна и Сергей Литвиновы - Литвинова Анна Витальевна (Звездный тандем российского детектива, 2014)
Экземпляры: Ф. 13 (20200129) / Инвентарный номер: 47560 / Цена: 50.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Л 64 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44